Individual differences in responsiveness to oral sensations and odours with chemesthetic activity: Relationships between sensory modalities and impact on the hedonic response. (March 2021) - Piochi, Maria; Dinnella, Caterina; Spinelli, Sara; Monteleone, Erminio; Torri, Luisa
Highlights: Subjects highly responsive to basic tastes are also highly responsive to astringency, pungency, PROP. Oral responsiveness is related to responsiveness to odorants with trigeminal activity. Oral irritation (capsaicin) and nasal irritation (odorants with chemesthetic activity) are correlated. Hyper-responsive subjects have a higher hedonic variation (span in liking ratings) Less responsive subjects require greater modifications in products to modify their liking. Abstract: Independent sensory modalities are related and showed covariations in prior literature. However, little is known on the relationship between oral sensations and nasal chemesthesis. This large-scale study aims (I.) to test the hypothesis that response to oral stimuli is related to responsiveness to odours with chemesthetic activity; and (II.) to explore the implications of these relationships on liking. Oral and olfactory responsiveness of 2205 Italians (18–65 years, men = 41%) were evaluated. Intensities of tastes, astringency and pungency were collected in water solutions and in four foods modulated for target sensations. Responses to bitterness of 6-n-propylthiouracil (PROP) was measured. Odour intensity and irritation were assessed for three pure odorants (L-Menthol, trans -anethole, (+)-α-Terpineol) stimulating nasal chemesthesis (respectively: TRPM8, TRPA1, TRPA1). Liking for odours and foods was measured. Specific intensity indices were developed for each sensation. Three clusters were identified based on taste intensity responses (Cl1, Cl2, Cl3). Cl1 (38%) was the most responsive to tastes, astringency, pungency, PROP and odours' intensity and irritation. This hyper-responsive cluster showed the highest hedonic variation (the span of liking ratings for stimuli with varied tastant concentrations). Cl2 (24%) was intermediate for oral responsiveness (apart for sourness) and Cl3 (38%) was the least responsive. Cl2 and Cl3 did not differ in odours' responsiveness (neither for perceived intensity nor for irritation). All sensory modalities were correlated but cross-correlations were higher when stimulating the same peripherical areas (oral vs oral more correlated than oral vs nasal). Results corroborate the idea of an overall high 'sensory responsiveness' covering different sensory modalities. Practical implications of the study are that less responsive subjects might require greater modifications in products formulations to modify their liking.